Analisis Kepuasan Konsumen Memediasi Pengalaman Belanja Online Dalam Membentuk Loyalitas Pelanggan (Survei E-Commerce Bukalapak) - Surahman, Zakilla Stephania; Sunarya, Ery (Jurnal Ilmiah Wahana Pendidikan, 2024)
Current technological developments require every human being to continue to innovate, including when it comes to shopping with the aim of making it easier and faster. e-commerce is one solution to overcome the problem of efficiency in carrying out buying and selling transactions. So Bukalapak e-commerce is one e-commerce that is not always people's main choice in using e-commerce because of the large number of e-commerce that currently exist. Thus, this will have an impact on decreasing consumer loyalty towards Bukalapak e-commerce. The purpose of this research is to determine the mediating influence of consumer satisfaction in the relationship between online shopping experience and customer loyalty interest. The results show that Bukalapak e-commerce has succeeded in building a good online shopping experience, consumer satisfaction and customer loyaliy in the eyes of consumers.